Kruszenie muru. O wpływie niezależnych ośrodków informacyjnych i wydawniczych na politykę kulturalną PRL - Tatarowski, Konrad W. (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2018)
The author of the article reminds us about the most important phases of the fight for freedom of speech in Poland between 1945 and 1989, during the time when the country was under Soviet influence. It indicates a broad public support of the activities of Radio Free Europe, which broadcast its programmes from Munich as well as support for various independent artistic and publishing initiatives in the country during that time. It also indicates the influence of independent information and cultural hubs on those media that were organised in a central doctrine according to marksist-leninist rules.